The Role of Indonesian Diplomacy in Managing the Conflict between The Myanmar Government and The Rohingya Muslim Ethnic - Sulaiman Rasyid; Adya Paramita Prabandari; Bastian Chris Daren; Christopher Simanjuntak (Unnes Law Journal, 2022)
The Rohingya population after Myanmar's independence has experienced a continuous decline this is due to several actions ranging from deportation to killings, until now only a few Rohingya Muslims remain in Rakhine. Basically, the conflict between the Rohingya and Rakhine is more about race than religion. The United Nations (UN) said that the Rohingya are the most oppressed ethnic group in the world. The purposes of this research are beside to analyze the role of Indonesian diplomacy in overcoming the conflict between the Rohingya Muslim Ethnic and the Myanmar Government, it also analyze the Indonesian government effort on Rohingnya case in the perspective International Law. The diplomatic strategy carried out by Indonesia in the issue of the Rohingya ethnic conflict with the Myanmar government, namely the submission of a humanitarian proposition and the proposed equation 4 + 1 for the Rohingya community in the future. Then, Indonesia also used the OIC as the largest international Islamic organization to pressure and urge Myanmar to immediately resolve the violence against the Rohingya. Lastly, diplomacy in the form of providing strategic assistance to the Rohingya ethnicity and participation of the Indonesian people in voicing the resolution of the conflict in Myanmar with the mass media.